The Evolution of the International Economic Order - Lewis, W. Arthur (William Arthur), 1915-1991 (Book collections on Project MUSE., 1978)
Do rich industrial nations underestimate the threat to their economic stability posed by demands for a new international economic order? Are the developing countries wrong to assume that their economic advancement depends on a transfer of wealth from the richer nations? Sir W. Arthur Lewis's provocative analysis of the present economic order and its origins suggests that the answer to both questions is yes. Professor Lewis perceptively illuminates aspects of recent economic history that have often been overlooked by observers of international affairs. He asks first how the world came to be d.